How Do Hurricanes Impact Achievement in School? A Caribbean Perspective - Nekeisha Spencer; Solomon Polachek; Eric Strobl (Institute for the Study of Labor (IZA), 2016)
This study examines whether hurricanes have any impact on performance in standardized examinations. The analysis uses a panel of thirteen Caribbean countries and over 800 schools for the period 1993 through 2010. In particular, the effect on subjects in the humanities and sciences are examined. A generalized difference-in-difference technique is utilized to study the relationship at the school, parish, year and country level. The results show a negative and significant effect on performance in the sciences if hurricanes strike when school is in session and a positive or no effect when school is not in session. In addition, subjects in the humanities remain unaffected.
Keywords: I2; Q54; 330; rate of return; human capital; hurricanes